陆军某部官兵创伤后应激障碍患病情况及其与功能性胃肠病的关系 - WANG, Qian; YAO, Xin; Hai-feng, JIN; SUN, Rong; YU, Jia; Jia ZHI; Chun-hua, WANG; Li-li, GUO (Jie fang jun yi xue za zhi, 2018)
Objective To determine the prevalence of post traumatic stress disorder (PTSD) in the army officers and soldiers (AOSs), and identify its relationship with functional gastrointestinal disorders (FGIDs). Methods PTSD and FGIDs were diagnosed based on the PTSD checklist-civilian (PCL-C) and Rome Ⅲ Modular Questionnaire respectively, the overlaps of PTSD and FGIDs and their correlation were diagnosed. The correlation of PTSD with traumatic and stressful events was investigated using Trauma History and Stressful Event Screening Questionnaire. The coexistence and relationship of PTSD and FGIDs were analyzed. Results Of 927 AOSs, 33 were diagnosed with PTSD. The prevalence of PTSD was 3.56%. FGIDs were identified in 435 subjects and the incidence of FGIDs was 46.93%. Among 33 AOSs with PTSD, 28 were diagnosed as having FGIDs and the prevalence of FGIDs was 84.85%, which was significantly higher than that of non-PTSD group (45.53%, P<0.05). Moreover, the FGIDs group had a higher prevalence of PTSD, compared with the